The mechanism of miR-155 targeting PIK3R1 in the pathogenesis of preeclampsia - Yi Zhou; Qiu Lian Xu (Scientific Reports)
Abstract To explore the molecular mechanism of miRNA-155-5p regulating placental trophoblast cell function and affecting preeclampsia. RNA was measured via RT-qPCR, and protein was detected with Western blot as well as Immunohistochemistry. Cell viability, proliferation, migration as well as invasion were detected via CCK8 assay, EDU stain as well as Transwell. Tunel assay measures cell apoptosis. Dual-Luciferase Reporter Assay affirms targeting relationships of miRNA-155-5p and PIK3R1. MiR-155-5p in PE patients’ placental trophoblasts was markedly higher, while PIK3R1 was lower. Knockdown of miR-155-5p in trophoblast enhanced cell viability, proliferation, migration as well as invasion, while reducing apoptosis. The predicted target gene of miR-155-5p was PIK3R1, while PIK3R1 expression was inversely correlated to miR-155-5p in HTR-8/SVneo. In trophoblast overexpressing miR-155-5p, increased PIK3R1 expression could reverse the effect. We confirmed that miR-155-5p affects the function of placental trophoblast HTR-8/SVneo, and confirmed that miR-155-5p affects the development of PE by regulating PIK3R1, which provides a target for treatment as well as prevention of PE.